Fingolimod's Impact on MRI Brain Volume Measures in Multiple Sclerosis: Results from MS‐MRIUS. Issue 4 (11th May 2018) - Zivadinov, Robert; Medin, Jennie; Khan, Nasreen; Korn, Jonathan R.; Bergsland, Niels; Dwyer, Michael G.; Chitnis, Tanuja; Naismith, Robert T.; Alvarez, Enrique; Kinkel, Peter; Cohan, Stanley; Hunter, Samuel F.; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Evidence is needed to understand the effect of fingolimod on slowing down brain atrophy progression in multiple sclerosis (MS) patients in clinical practice. We investigated the effect of fingolimod on brain atrophy in MS patients with active disease (clinically and/or magnetic resonance imaging [MRI]) versus no evidence of active disease (NEAD). METHODS: MS and clinical outcome and MRI in the United States (MS‐MRIUS) is a multicenter, retrospective study that included 590 relapsing‐remitting MS patients, who initiated fingolimod, and were followed for a median of 16 months. Patients with active disease at baseline (245, 41.5%) were defined as those who had one or more relapses in the year previous starting fingolimod, and/or displayed gadolinium enhancing lesions(s) at baseline MRI scan, whereas patients with NEAD at baseline (345, 58.5%) did not fulfill these criteria. Annualized percentage brain volume change (PBVC) and percentage lateral ventricle volume change (PLVVC) over the follow‐up were analyzed in both groups. RESULTS: Over the follow‐up, the rate of PBVC was −.38% in active disease and −.25% in NEAD patients ( P = .076), whereas PLLVC was 1.76% in active disease and .28% in NEAD patients ( P = .046). No changes in timed 25‐foot walk ( P = .619) and Expanded Disability Status Scale ( P = .275) scores or MRI lesion accumulation ( P > 0.08) were detected, although the active disease group had a higher proportion of relapses during the follow‐up period ( P = .02). CONCLUSIONS: The study provides real‐world evidence that rate of brain atrophy in MS patients with underlying active disease and NEAD in fingolimod treated patients is below the established pathological cutoff for loss of whole brain volume (>−.4%) or expansion of lateral ventricles (> 3.5%).